Sharing the benefits from water as a new approach to regional water targets for mining companies - Kunz, N.; Moran, Chris (Elsevier, 2014)
© 2014 Elsevier Ltd. All rights reserved.Most major mining companies have articulated strategies and targets to minimise the impacts of operations on surface and groundwater resources. However, the focus tends to be on mitigating negative impacts. In this field note, we make two contributions to assist mining sites in playing a positive role in implementing Integrated Water Resources Management (IWRM) aspirations. First, we introduce the notion of "water benefits" as a pathway for operationalizing regional IWRM objectives at a mine site level. Second, we propose a decision making framework to facilitate investment in water benefits. The framework comprises of five steps: (1) Select system boundary wherein benefits are to be delivered; (2) Quantify water availability; (3) Determine potential benefits; (4) Identify acceptable benefits; and (5) Implementation and monitoring. For a site to deliver water benefits that extend beyond the legal obligation of the company, we contend that there must be a sound business case. We therefore distinguish between steps that should be decided by the business (steps 1, 2 and 4) from those that should be completed in collaboration with the broader community (steps 3 and 5). Within this field note we do not test the practical utility of the framework in an empirical setting and as such it is not intended to be prescriptive. Rather, we seek to provide a foundation for scholarly/industry debate about how decision makers at a mine site level could take a more active role in contributing towards IWRM aspirations. We conclude that a "water benefits" perspective offers a novel basis for establishing regional water targets and could serve numerous advantages at a site-level including improved recognition about the value of water and improved understanding and mitigation of strategic water-related risks.